Wirtschaftsgeschichte Die Entstehung der modernen Volkswirtschaft - Pierenkemper, Toni; Pierenkemper, Toni (Akademie Studienbücher - Geschichte, 2015)
In the revised edition of the textbook on economic history, Toni Pierenkemper portrays transformations in economic structure (from agrarian to industrial society and to a service society) as well as the economic growth and prosperity resulting from the industrial revolution. He describes in detail the emergence of the labor market as well as the nexus of capital and banks, money and currency.